HERMENEUTIKA EKO SUFISTIK AL-QUSYAIRI DAN IBNU ‘ARABI : TELAAH MAKNA KATA AL-FAHSA’ WA AL-MUNKAR - Amelia Putri (Jurnal Intelek Insan Cendikia, 2025)
The increasingly complex ecological issues have become a major focus in global discussions. However, ecological studies are often detached from spiritual dimensions, even though the values of worship in Islam hold potential for fostering ecological awareness. This article explores the meanings of the terms al-fahsya’ and al-munkar in Surah Al-Ankabut verse 45 through the lens of Sufi hermeneutics, as interpreted by Al-Qushayri and Ibn ‘Arabi. The study aims to uncover the connection between morality, spirituality, and ecological awareness. Using a qualitative method based on library research, this study analyzes Qur’anic exegesis and Sufi literature. Al-Qushayri interprets al-fahsya’ as external dimensions, such as the world and immoral deeds, while al-munkar encompasses inner drives (nafs). Ibn ‘Arabi defines al-fahsya’ as the visible impacts of damage and al-munkar as something rejected by the heart. Both scholars agree that the spiritual and moral dimensions of worship, like prayer, can prevent ecological and moral damage. The findings underscore the importance of integrating spirituality and ecological awareness to preserve environmental harmony. Sufi hermeneutics provides a holistic understanding of al-fahsya’ and al-munkar and their relevance to environmental sustainability. Keyword : Ecospiritual Hermeneutics, Al-Qusyairi, Ibnu ‘Arabi, Al-fahsya' wal-munkar